Respostas

2013-07-03T12:49:17-03:00

Por adição: 

(2x-2y= 12) x (-1)

-2x+2y = -12

{

x-2y = 11

_____________

-x = -1

x = 1

_____________

substitui p/ descobrir Y

1-2y =11

-2y =11 -1

- 2y = 10

y = -5 

 

:)

 

1 5 1
2013-07-03T12:53:35-03:00

8x-3y=295 ( multiplique por 2)

9x+6y=555

________

16x-6y=295

 9x+6y=555

_________

25x+0 = 850

x= 850/25=

x-= 34

 

 

 

 

2x-2y=12

x-2y=11    ( multiplique por - 2)

_______

 

2x-2y=12

-2x+4y=22

________

0 2y= 10

    y= 10/2

     y= 5

1 5 1